2021
DOI: 10.1200/go.20.00665
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide, Thalidomide, and Dexamethasone as Initial Therapy for Patients With Newly Diagnosed Multiple Myeloma in a Middle-Income Country: 7-Year Follow-Up

Abstract: PURPOSE Major progress has occurred in multiple myeloma (MM) treatment in recent years, but this is not seen in low- and middle-income countries. MATERIALS AND METHODS We retrospectively assessed the efficacy and safety of cyclophosphamide, thalidomide, and dexamethasone (cyclophosphamide 400 mg/m2 for 5 days, thalidomide 100 mg once daily, if tolerated, and dexamethasone 40 mg once weekly; in 28-day cycles) in patients with newly diagnosed MM treated at our institution between April 2008 and December 2012. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…However, Vasquez et al reported a median OS of 81 months and a 5-year OS rate of 57.5% in a study from a middle-income country. 23 Furthermore, we did not see a survival difference between patients treated with CTD and BTD. Similar results were reported by Rosiñol et al The estimated OS rate at 4 years was 74% for patients treated with BTD, and there was no OS difference between BTD and other treatments groups.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…However, Vasquez et al reported a median OS of 81 months and a 5-year OS rate of 57.5% in a study from a middle-income country. 23 Furthermore, we did not see a survival difference between patients treated with CTD and BTD. Similar results were reported by Rosiñol et al The estimated OS rate at 4 years was 74% for patients treated with BTD, and there was no OS difference between BTD and other treatments groups.…”
Section: Discussionmentioning
confidence: 52%
“…An Iranian study has shown the median age of presentation to be 51 years, 22 and a Pakistani study has shown it to be 57 years. 20 In another study from Vasquez et al 23 from a middle-income country, the median age was 56 years and 59% were male. However, our data are similar to the data of an Asian Myeloma Network study, in which the median age of presentation was 62 years.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations